Beyond lost earnings: The long-term impact of jobdisplacement on workers' commuting behavior - Yige Duan; Oskar Jost; Ramona Jost (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
We study the long-term impact of job displacement on workers' commuting behavior. Our measures of commuting exploit geo-coordinates of workers' places of residence and places of work, from which we calculate the door-to-door commuting distance and commuting time. Using German employee-employer matched data and an event study design, we identify the causal effect of job loss on workers displaced during a mass layoff. Conditional on finding a new job, workers' commuting distance and commuting time rise sharply after displacement and gradually decline in subsequent years. The recovery is due to employer changes rather than migration, and a larger increase in commuting would mitigate the wage loss due to job displacement. To rationalize our findings, we build an on-the-job search model with heterogeneous firm productivity and commuting distances. Our model predicts a joint recovery of wages and commuting despite a static tradeoff between the two attributes.
Keywords: J3; J6; R23; R41; 330; commuting; mobility; displacement; job search